Pengaruh Likuiditas, Pertumbuhan Perusahaan, Ukuran Perusahaan terhadap Nilai Perusahaan dengan Profitabilitas sebagai Intervening - Anasya Risquita; Desi Ika (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2026)
This study aims to examine the effect of liquidity, company growth, and company size on firm value, with profitability as a mediating variable. These three independent variables are seen as internal factors that, theoretically, can influence firm value, both directly and indirectly through financial performance. This study employs a quantitative approach, using multiple linear regression analysis, path analysis, and Sobel tests to examine the mediation effect. The results show that liquidity has a significant effect on profitability, while growth and company size do not have a significant impact. Furthermore, the findings indicate that liquidity, growth, and company size do not directly affect firm value. However, profitability was found to significantly influence firm value and can mediate the relationship between liquidity and firm value. In contrast, profitability does not mediate the effect of growth or company size on firm value. These findings contribute to understanding the importance of profitability as a factor influencing firm value and provide insights into how internal company factors affect financial performance and firm value.